Analisis Kelayakan dan Sensitivitas: Studi Kasus Industri Kecil Tempe Kopti Semanan, Kecamatan Kalideres, Jakarta Barat - Etty Susilowati; Haruni Kurniati (Universitas Negeri Surabaya, 2018)
The small manufacturing sector has a large role in the processing of agricultural products and helps provide employment and business opportunities in an effort to encourage regional and rural development. The small industrial estate (PIK) of KOPTI Semanan in Kalideres Subdistrict, West Jakarta is one of the fermented soybean processing centers in Jakarta. In running its business, PIK KOPTI Semanan faces internal and external constraints so it has not been able to achieve business development as expected. The purpose of this research was to analyze the feasibility and sensitivity of small industry enterprises in Kalideres Subdistrict, West Jakarta. Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Net Benefit Cost Ratio (Net B/C) methods were employed to calculate the financial feasibility of small fermented soybean industry enterprises. While the sensitivity analysis is done by doing the scenario of decreasing and increasing cost and price. The results of the analysis indicated that the small fermented soybean industry in Kalideres District is feasible to be implemented. However, the sensitivity analysis results indicated 3 out of 5 enterprises were sensitive to decreased revenue and increased costs.